2019
DOI: 10.1038/s41390-019-0299-6
|View full text |Cite
|
Sign up to set email alerts
|

Timely initiation of breastfeeding among first time mothers in Bahir Dar city, North West, Ethiopia, 2016

Abstract: BACKGROUND: Timely initiation of breastfeeding is one important intervention to prevent childhood morbidities and mortalities. Globally, not more than 35 and 39% in developing countries, 52% in Ethiopia and 38% in Amhara region were initiated with breastfeeding early. METHODS: A community based cross-sectional study was conducted from 20 March to April, 2016. A total of 423 mothers who have infants less than 6 month old were included in this study. The data were collected using interviewer administered questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 18 publications
(24 reference statements)
2
13
2
Order By: Relevance
“…as compared to women who gave birth other than health institution. This is consistent with studies which have been conducted in South Gondar, Motta town and Bahir Dar [AOR 3.1; 95% CI 2.2, 4.6],[AOR = 3.486(1.253, 9.700)] and [ AOR 3.36; 95% CI 1.47,7.670] respectively (24,25,19).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…as compared to women who gave birth other than health institution. This is consistent with studies which have been conducted in South Gondar, Motta town and Bahir Dar [AOR 3.1; 95% CI 2.2, 4.6],[AOR = 3.486(1.253, 9.700)] and [ AOR 3.36; 95% CI 1.47,7.670] respectively (24,25,19).…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, the prevalence of timely initiation in this study was lower than the findings of studies done in Bahir Dar, Motta and Wolayita town in which timely initiation of breastfeeding was 75.4%, 78.8 % and 81.1% respectively (24,25,26).…”
Section: Discussioncontrasting
confidence: 84%
“…Following a rigorous screening, 28 studies were selected for fulltext review. Three studies were excluded after the full-text review: one study 19 reported only the prevalence of TIBF, and the other two studies 20,21 did not report the selected factors of our interest. A total of 25 studies were included in this meta-analysis, which most of them conducted on mothers with newborn <23 months.…”
Section: Search Resultsmentioning
confidence: 99%
“…Following a rigorous screening, 28 studies were selected for full text review. Three studies were excluded after the full text review: one study(56) reported only the prevalence of TIBF, and the other two studies(20, 57) did not report the selected factors of our interest. A total of 25 studies were included in this meta-analysis, which most of them conducted on mothers with newborn less than 23 months.…”
Section: Resultsmentioning
confidence: 99%
“…The age distribution of under-five deaths varies from 29% in the first 30 days of life to 42% in the fourth year. (20) Neonatal mortality rate is still high in Ethiopia, which accounts for 42% of under-five deaths. (21, 22) Based on our previous meta-analysis of 13 observational studies conducted in Ethiopia, the prevalence of neonatal mortality is 16.3%.…”
Section: Introductionmentioning
confidence: 99%